MUTU BIOPELET DARI BAGAS, KULIT KACANG TANAH DAN POD KAKAO - Alfian Syukri Lubis,Muhammad Romli, Mohamad Yani, Gustan Pari (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Agricultural biomass is a potential alternative energy’s sources that has not been well managed. The objectives of this research were to produce biopellet from bagase and peanut shell and to quantify the parameters quality of biopellet’s formulation. This research was started with bagasse, peanut shell, and cacao pod characterisation. Futhermore is milling prosess of raw material, formulation of raw material with addition material, densification process, drying, and analysis of chemical, physical, and biological quality of biopellet product.From the analytical results, the best biopellet’s formula was biopellet made from peanut shell 100% with heat value of 4644 kcal/kg, biopellet from bagasse Trangkil 40% and peanut shell 60% with heat value of 4584 kcal/kg, and biopellet from industrial small bagasse 40% plus peanut shell 60% with heat value of 4539 kcal/kg. Keywords: bagasse, biopellet, densification, peanut shell